Contributions of the cross phase to the plasma transport. (22nd September 2017) - An, Chan-Yong; Min, Byunghoon; Kim, Chang-Bae
Abstract: Numerical simulations of the resistive-drift plasma turbulence are performed in order to look into the effects of the E × B fluxes on the cross phase between the electric potential and the particle density. As the electrons become more adiabatic, it is found that the spectrum of the particle transport shifts away from the spectra of the energies. It is because the cross phases of the larger-scale ( k ρ s ≪ 1 ) fluctuations, ρ s being the ion gyro-radius defined by the electron temperature instead of the ion temperature, where most energies reside come to be vanishingly small in correspondence to the level of adiabaticity. The cross phase in the scale k ρ s < 1 is predominantly determined by the electron diamagnetic drift and the resistive current as the plasma is closer to be adiabatic. Advective parts of the E × B fluxes are found to reduce the cross phase and their effect is more pronounced as k ρ s ≥ 1 .